Client-auditor realignment and restrictions on auditor... - Chancy, Paul K.; Jeter, Debra C.; Shaw, Pamela Erickson (The Accounting Review, 1997)
We compare clients' realignment decisions in markets permitting direct uninvited solicitation (allowed markets) and markets prohibiting such practices (banned markets), providing insight into the effects of increased competition on client-auditor alignment. We argue that solicitation influences realignment decisions if clients do not invite nonincumbents to submit proposals, and if net economies are available (i. e., the cost savings from switching auditors exceeds any transactions costs incurred in realignment). By examining realignments among Big 8 auditors during the period 1980 through 1988, and by controlling for other variables associated with auditor switching, we are able to focus on the effects of solicitation in a setting of homogeneous audit quality and diversity in state boards' direct solicitation rules. We find that realignment occurs more frequently in the allowed market than in the banned market. Thus, in markets where auditors are allowed to approach prospective clients with proposals, clients become better informed and the outcome may be reduced inefficiencies.